Governança das águas no Brasil : a aplicação da Política Nacional de Recursos Hídricos e seus impactos no território da bacia do rio São Francisco - Palma, Eduardo Gabriel Alves (2017)
The reduction in the supply of good quality water of environmental quality has caused signs about the importance of the protection of the surface water supply and underground. In this sense, the emergence of measures to control and control the use of water resources in various parts of the world has forced a major debate, namely: who is responsible for water governance? In this context, the present research deals with the pillars of water governance in Brazil, and, specifically, in the São Francisco river basin, with the general objective of analyzing the impact of the application of the National Water Resources Policy in that basin and its Consequent refusal in the territory. In the first moment a bibliographical survey of authors dealing with the subject and official documents on water governance in the national territory and in the research area, such as Development Plans, Executive Plans, international, national and regional regulatory frameworks, As well as its application in the hydrographic unit. The survey of primary data in the field consolidated the empirical discussion of the subject, when the elements of governance that are in conflict for the appropriation of land and water are verified. These aspects helped to a theoretical-methodological reflection on the water governance in Brazil and its impacts in the territory of the São Francisco basin, interacting with authors specialized in the subject and of several areas of knowledge, addressing three fundamental aspects, namely: a) The river basin as the preferred unit of water planning and management; B) Principles and Fundamentals of water governance in Brazil and the São Francisco River; and c) The granting of resources as an instrument of selective access to water resources. In addition, it is observed that the use of water by all segments of users has caused unequal and asymmetric access to this resource through the reservation and authorization through grant and collection by the National Water Agency when using the reference flow Of the river basin, and its impact on the territory and governance of the São Francisco waters.